Effects of recycled organic waste in soilless growing medium on the growth and flowering of Gerbera (Gerbera jamesonii Bol.) in pot culture - Ali Mahboub Khomami; Abdullah Hatamzadeh; Hosein Jafari Khaljiri (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Cocopeat resources in Iran are limited and unsuitable, and they must be imported from abroad at a high cost. It is therefore essential to evaluate suitable growth media to replace cocopeat. Method: During this experiment, we conducted a completely randomized experimental design with seven types of growing media in a greenhouse with two layers of hexane coating, at the flower and ornamental plant research station in Lahijan city. Seven growth substrate treatments were investigated, including: (100%perlite), (75%cocopeat + 25%perlite), (50%tea waste + 25%peanut shells compost + 25%perlite), (50%tea waste +%25 Azolla + %25 Perlite), (50%peanut shells compost + 25%azolla + 25%perlite), (50%peanut shells compost + 25%tea waste +25% azolla) and (25%peanut shells compost + 25%tea Waste + 25%azolla + 25%perlite). Results: According to the results, growth media containing peanut shells, Azolla composts, and tea waste are effective and recommended, which can significantly reduce the use of cocopeat. A substrate containing compost had a better effect on the morphological and physiological characteristics of Gerber. Conclusion: The yield of Gerbera varied greatly among growth substrates, and flower performance was better in some substrates than in cocopeat. The favorable effect of composted substrates on Gerbera yield allows the selection of the growth substrate.